ZnO nanorods modified with noble metal-free Co3O4 nanoparticles as a photocatalyst for efficient ethylene degradation under light irradiation. Issue 21 (16th October 2019) - Cui, Zihao; Liu, Xiaolei; Liang, Xizhuang; Wang, Peng; Zhang, Qianqian; Wang, Zeyan; Zheng, Zhaoke; Liu, Yuanyuan; Dai, Ying; Huang, Baibiao
Abstract : ZnO modified with noble metal-free Co3 O4 nanoparticles was prepared by a simple method and showed good stability and high efficiency for photo-oxidizing ethylene. Abstract : In this study, we synthesized noble metal-free Co3 O4 as a cocatalyst for a modified ZnO nanorod photocatalyst to achieve efficient ethylene degradation under light irradiation. The Co3 O4 -decorated ZnO nanorods demonstrate photocatalytic activity for ethylene oxidation that is better than that of pure ZnO and even better than that of the noble metal-based RuO2 -modified ZnO. Furthermore, Co3 O4 -modified ZnO exhibits good stability in a six-cycle experiment. Measurement results indicate that the Co3 O4 nanoparticles can effectively promote the transfer and inhibit the recombination of photogenerated electrons and holes during the photocatalytic reaction. Therefore, the Co3 O4 -modified ZnO nanorod photocatalyst displays excellent photocatalytic properties for ethylene degradation and can effectively realize the complete mineralization of ethylene molecules.